2022
DOI: 10.1111/1753-0407.13248
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between creatinine to body weight ratios and diabetes mellitus: A Chinese cohort study

Abstract: Background: Research on the relationship between creatinine to body weight ratios (Cre/BW ratios) and the prevalence of diabetes is still lacking. The intention of this research was to explore the potential relationship between Cre/BW ratio and diabetes prevalence in Chinese adults.Methods: This retrospective study was conducted on 199 526 patients in the Chinese Rich Healthcare Group from 2010 to 2016. The participants were divided into four groups on the basis of the quartiles of the Cre/BW ratios. Multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…Identifying the Cre/BW ratio as a protective factor for developing diabetes in pre-diabetes and clarifying the association between them will benefit diabetes prevention in patients with pre-diabetes. Also, the HRs of the relationship between creatinine body weight ratio and diabetes were different in our study from that of Chen et al [ 20 ].…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Identifying the Cre/BW ratio as a protective factor for developing diabetes in pre-diabetes and clarifying the association between them will benefit diabetes prevention in patients with pre-diabetes. Also, the HRs of the relationship between creatinine body weight ratio and diabetes were different in our study from that of Chen et al [ 20 ].…”
Section: Discussioncontrasting
confidence: 97%
“…A Chinese study also found an inverse association between the Cre/BW ratio and the risk of diabetes in the general population (HR = 0.268, 95%CI 0.229–0.314) after adjusting confounding variables. They also found a negative non-linear connection between the Cre/BW ratio and incident diabetes [ 20 ]. By Cox proportional hazards regression model analysis, our study found that the decline in the Cre/BW ratio was strongly associated with an increased risk of diabetes, which was consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations